Penerapan Rendam Air Hangat dan Foot Massage pada Pasien Hipertensi - Yohana Ani Suprapti; Sri Indaryati; Srimiyati Srimiyati (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2026)
Complementary therapy has recently become an important issue in many countries. Its use has increased due to several factors, including personal beliefs, cost considerations, the side effects of chemical medications, and expectations of recovery. One of the complementary therapies that is often chosen is warm water foot soaking combined with foot massage. This therapy has the potential to reduce blood pressure through relaxation mechanisms and peripheral vasodilation, which have been supported by scientific evidence.This study aimed to analyze the application of Evidence-Based Practice (EBP) of warm water foot soaking and foot massage therapy in hypertensive patients within nursing care. The method used was an EBP-based case study design involving three patients with hypertension. The intervention consisted of warm water foot soaking using approximately 2 liters of water at a temperature of 38–40°C combined with foot massage, administered once daily for three days. Blood pressure was measured before and after the intervention.The results showed a decrease in blood pressure: Mrs. S from 170/100 mmHg to 150/80 mmHg, Mrs. L from 170/80 mmHg to 150/80 mmHg, and Mr. F from 165/90 mmHg to 130/70 mmHg. Warm water foot soaking and foot massage were effective as non-pharmacological interventions to reduce blood pressure and improve comfort in patients with hypertension. ase study design involving three patients with hypertension. The intervention consisted of warm water foot soaking using approximately 2 liters of water at a temperature of 38–40°C combined with foot massage, administered once daily for three days. Blood pressure was measured before and after the intervention.The results showed a decrease in blood pressure: Mrs. S from 170/100 mmHg to 150/80 mmHg, Mrs. L from 170/80 mmHg to 150/80 mmHg, and Mr. F from 165/90 mmHg to 130/70 mmHg. Warm water foot soaking and foot massage were effective as non-pharmacological interventions to reduce blood pressure and improve comfort in patients with hypertension.